Pengaruh Kualitas UI/UX Website dan Copywriting terhadap Brand Awareness Konsumen Fashion Digital : Studi pada Website UNIQLO di Kota Denpasar - Kadek Agus Jovi Oka Suputra; Gede Yudha Anugerah Pratama; I Made Satrya Ramayu (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
The rapid development of digital technology has transformed websites into strategic tools for marketing communication and brand development. In the highly competitive fashion industry, website quality and digital communication effectiveness are essential factors in strengthening consumers’ brand awareness. However, limited studies have simultaneously examined the influence of User Interface/User Experience (UI/UX) Website and Copywriting on Brand Awareness, particularly in the context of global fashion brands. Thus, the purpose of this study is to examine how copywriting and UI/UX websites affect brand awareness among users of the main UNIQLO website in Denpasar. Using primary data gathered from 110 respondents via questionnaires, this study used a quantitative explanatory technique. With the use of SPSS software, descriptive statistics and multiple linear regression analysis were used to analyse the data. The findings show that brand awareness is positively and significantly impacted by UI/UX websites (β = 0.175; p = 0.019) and copywriting (β = 0.727; p = 0.000). Furthermore, Copywriting was identified as the most dominant variable influencing Brand Awareness. The coefficient of determination (R²) of 0.752 indicates that 75.2% of the variation in Brand Awareness can be explained by UI/UX Website and Copywriting. The findings conclude that both website quality and communication quality play important roles in shaping consumers’ awareness of the UNIQLO brand. This study implies that companies should integrate UI/UX development and effective copywriting strategies to enhance digital marketing performance and strengthen brand awareness in competitive digital environments.